Design and implementation of the control system on-off the laser projector Lasiris Magnum II for SICAIPAV II system (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2016)
Automatic inspection systems use laser technology pavements for collection pavement damage generating three dimensional images of high precision. However, depending on the category of laser may cause injury to people or animals. In Colombia, the automated system SICAIPAV 11 is developed for collecting three dimensional data of paved roads using a class IIIB laser projector. Maintain safety of operators and bystanders, and comply with Colombian law occupational safety and welfare are an indispensable requirement surveying in the field. This paper presents the design and implementation of a control electronic system for on-off laser projector automatic system using ultrasonic sensors, an encoder and an Arduino development board. The control system is coupled on the back of a vehicle and allows turned on or off the laser depending on the vehicle speed or proximity of people within an area approximately 3 m2. Finally, experimental tests demonstrate the effectiveness of the system, with coverage of 52,9% of the area of risk and delay times 1,13 S.
Keywords: Control system; ultasonic sensor; relative encoder; Arduino development board